Low-Cost Method to Volumetric Computed Aided Planning of Posttraumatic Sequelae in Orbito-Zygomatic Reconstruction: A Case Report - Araújo, Marcelo Marotta [UNESP]; Gabrielli, Mário Francisco Real [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP]; Sato, Fábio Ricardo Loureiro; Bártholo, Paulo Roberto De Alencar; Carvalho, Pedro Henrique De Azambuja [UNESP] (SAGE Publications, 2022)
Study design: The present case report demonstrated a reproducible and low-cost method to planning orbito-zygomatic reconstruction applied to a sequela of facial trauma. Aim: This study aims to purpose a method to surgical planning orbito-zygomatic reconstruction and demonstrate it in a clinical report. Method: An 89 years old male patient with severe sequela due to previous trauma surgery was submitted to a reconstructive surgery using cutting guides and mini-plates pre shaped using a stereolitographic printed model with mirroring healthy side. Results: Computed assisted surgery (CAS) contributed to the advancement of surgical planning and reconstruction in Oral and Maxillofacial Surgery, and trauma-related injuries. Traumatic injuries at the orbito-zygomatic region and midface are challenging and satisfactory three-dimensional reconstruction is not often achieved with conventional techniques; therefore, it strongly benefits from CAS and 3D printing. However, the high costs and technical difficulties can impair the use of new technologies in the public health system of low-income countries. Conclusion: Hence, the present case report demonstrated a reproducible and low-cost method to planning orbito-zygomatic reconstruction applied to a sequela of facial trauma.
Keywords: 3D printing; case report; computed assisted surgery; orbito-zygomatic reconstruction